“Torna-te quem tu és”: o bordado como potência para o empoderamento da mulher, em interface com a pintura e outras linguagens - Paula, Thalita Ellen Freitas de (2018)
This monograph aims to discuss the position of embroidery in the hierarchy between textile art and academic art, and the subjugation of this technique due to the fact of it being a typically-feminine technique because of its utilization mostly by women, from the beginning of embroidery applications until it becomes a form of artistic expression in contemporaneity. This research is constructed through a series of works titled “Torna-te quem tu és” which explore a variety of representation of the feminine body, aiming to support women empowerment. Interweaved on the canvas are all these issues and my own way of dealing with the objections presented when it comes to the technique of embroidery in combination with the hybridism of other techniques, such as painting, drawing, engraving, and fabric applications as expressive materials. Exploring, within this context, the social pressure exerted against the feminine gender and my own experiences within these universes as a woman and an artist.